2009
DOI: 10.1128/iai.00570-09
|View full text |Cite
|
Sign up to set email alerts
|

Infection withAnaplasma phagocytophilumInduces Multilineage Alterations in Hematopoietic Progenitor Cells and Peripheral Blood Cells

Abstract: Infection withHematopoietic lineage assessment demonstrated that there was loss of erythrocytes and B lymphocytes from the BM along with increased granulopoiesis. These changes were accompanied by splenomegaly due to lymphoid hyperplasia and increased hematopoiesis, most notably erythropoiesis. These changes largely mimic well-described inflammation and endotoxin-mediated effects on the BM and spleen; however, the numbers of peripheral blood neutrophils appear to be independently modulated as granulocytic hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 61 publications
5
54
0
Order By: Relevance
“…Inflammation-mediated changes would increase the release of myeloid and nonmyeloid cells for pathogen colonization. This line of thinking is supported by recent studies showing that A. phagocytophilum causes hematopoietic alterations in the spleen, with an expansion of lymphoid follicules and marked extramedullary hematopoiesis in the red pulp (26,27). Hematopoietic changes were characterized by increased numbers of Ter-119 ϩ erythroid precursors, B lymphocytes, and Gr-1 ϩ granulocytic cells postinfection.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Inflammation-mediated changes would increase the release of myeloid and nonmyeloid cells for pathogen colonization. This line of thinking is supported by recent studies showing that A. phagocytophilum causes hematopoietic alterations in the spleen, with an expansion of lymphoid follicules and marked extramedullary hematopoiesis in the red pulp (26,27). Hematopoietic changes were characterized by increased numbers of Ter-119 ϩ erythroid precursors, B lymphocytes, and Gr-1 ϩ granulocytic cells postinfection.…”
Section: Discussionsupporting
confidence: 63%
“…This clear-cut dichotomy suggests that some genes in the A. phagocytophilum genome may contribute to pathogen colonization while others may be directly associated with the disease state in mammals. The latter are clinically relevant because cytopenias and splenomegaly-common HGA symptoms-are largely due to host inflammation (16,26,27,56). In this study, we characterized the molecule LPDA1 during A. phagocytophilum colonization of the mammalian host.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…phagocytophilum infection in mice induces the delayed and weak expression of TNF-␣ and IL-6 and significant expression of MIP-2, KC (mouse IL-8 homologs), and JE (mouse MCP-1 homolog) in the bone marrow (106), similar to that observed for human bone marrow or HL-60 cells (115). As the exposure of bone marrow cells to chemokines (e.g., IL-8 and MIP-1) suppresses the proliferation of myeloid progenitor cells (35), alterations in chemokine levels in the bone marrow were proposed to be responsible in part for the hematological abnormality that accompanies A. phagocytophilum infection (106).…”
Section: Roles Of Ifn-␥ and Il-8mentioning
confidence: 82%
“…Thus alterations in PMN behavior in the seconds following contact with extracellular A. phagocytophilum may be relevant to PMN trafficking. Pathogen-induced changes in PMN trafficking in vivo are currently being studied in mouse models of infection (8,29,32). We have observed that differential trafficking with prominent PMN migration to and accumulation within the spleen occurs during infection (Borjesson et.…”
Section: Discussionmentioning
confidence: 95%